Tricky twenty-two - Evanovich, Janet (New York : Bantam Books, 2015)
Stephanie Plum might not be the worlds greatest bounty hunter, but she knows when shes being played. Ken Globovic (aka Gobbles), hailed as the Supreme Exalted Zookeeper of the animal house known as Zeta fraternity, has been arrested for beating up the dean of students at Kiltman College. Gobbles has missed his court date and gone into hiding. People have seen him on campus, but no one will talk. Things just arent adding up, and Stephanie cant shake the feeling that something funny is going on at the collegeand its not just Zeta fraternity pranks.
Includes an excerpt from The scam (pages [285]-292)
Keywords: Private investigators -- Fiction; Women detectives -- Fiction; Plum, Stephanie (Fictitious character) -- Fiction; New Jersey -- Fiction; Mystery fiction; Humorous fiction; Detective and mystery fiction